Impact of music education on musical perception in professional musicians, amateur musicians, and non-musicians (Research, Society and Development, 2022)
Musical perception is directly related to music education, which is influenced by several factors. This perception needs to be objectively characterized in the Brazilian population since there is no standard of music education applied equally by different training centers. The objective of the present study was to evaluate the musical perception of the Brazilian population through the Music Ear Test (MET) of professional, amateur, and non-musician musicians. The test effectively separated the group of professional musicians from the other groups. In the group of professional musicians, performance on the rhythmic subtest negatively correlates with age. In the group of amateur musicians, the performance in the melodic subtest was positively correlated with hours of musical study. The group of non-musicians was the only one in which the performance in the two sub-tests, melodic and rhythmic, was positively correlated.